National parks policy and planning: a comparative analysis of friluftsliv (Norway) and the dual mandate (New Zealand). Issue 2 (3rd May 2016) - Higham, James; Vidar Haukeland, Jan; Hopkins, Debbie; Inge Vistad, Odd; Lindberg, Kreg; Daugstad, Karoline
ABSTRACT: Conservation management in Norway is anchored in the historical tradition of friluftsliv although Norway's evolving economic policy signals that growing priority is being given to recreation and nature-based tourism development in association with protected natural areas (PNAs). Here we present the results of an international comparative study that examined conservation policy and recreation/tourism management in Norway and New Zealand, where a legislated dual mandate of conservation and tourism in PNAs is longstanding. Our analysis of conservation policy and planning documents in Norway and New Zealand highlights important contrasts in conservation and recreation/tourism management that are deeply embedded in national socio-historical contexts. Our findings highlight lessons that may be learned and applied in Norway. However we also caution that the application of lessons from New Zealand's 'utilitarian conservation' policy context may require a reformulation or refinement of the friluftsliv tradition.